Study The Side Effects Of Administration Of A Traditional Product For Weight Gain In Albino Rats (Journal of Pharmaceutical Negative Results, 2022)
The modern studies on the treatment of excessive thinness have dedicated on the potential activity of plants to increases appetite. The aim of this study is to investigate the effect of Puma as a weight gain product and nutritional supplement on body metabolism on its administers and determine its safety. 9 male rats were weighted (130 to 190 g) and divided equally into 3 groups, the first group considered as control group and administered distilled water, the two other groups divided into a single dose group and a double dose group. Administered the prepared aqueous solution of puma fat face pills for 30 days. The animals weighed after 24 hr. of the last administration. The results showed after weeks of treatment that the animals didn't gain much weight compared to control group and there were no beneficial effects of this product. AST & ALT levels was high in the single and double dose group also there is a change in the levels of creatinin while the urea level didn’t change, the hisopathological study showed bleeding in kidneys and liver and more damage in these organs.